Left behind: exploring how mainstream social work students see themselves compared to the 'best and brightest'. Issue 4 (19th May 2022) - Hanley, Joe
ABSTRACT: Over the past ten years, fast-track social work qualifying training routes have been introduced and rapidly expanded in England. These programmes justify their existence through rhetoric that implies their students are superior to other students, and therefore require special privilege—the 'best and brightest'. When evaluating fast-tracks, the approach taken largely ignores their broader public impact, including how they impact on the majority of social work students who continue to qualify through mainstream university social work education. This exploratory study seeks to gain an understanding of the impact that these changes have had on mainstream social work students, and in particularly how these students see themselves in relation to fast-track students. Based on the principles of democratic evaluation, brief and anonymous questionnaires were sent to all postgraduate social work students at two universities in England. The findings suggest that while mainstream students do not generally perceive themselves as being inferior future practitioners, they do recognise the financial and symbolic inequity they are subjected to, in particular as a result of their qualifying courses receiving significantly less financial support. Findings related to participants' reasoning for not applying to fast-tracks, and how views differ based on demographics, are also explored.